Applying the Life Design Model (LDM) to the career development of Swazi women from polygynous family settings - Dlamini, Nontobeko. G (My University, 2015)
The aim of the study was to apply the Life Design Model (LDM) as a career counselling intervention to the lives of 10 Swazi women from polygynous family settings experiencing career development challenges at work. The intervention sought to mitigate the effects of cultural values associated with polygyny that interfered with career life design choices and development among employees. Life designing, within this study was conceptualised as the approaches and strategies utilised by individuals to manage and negotiate their multiple subjective identities. This study used a qualitative research method. The 10 Swazi women were selected through convenience and snowball sampling methods and met the selection criteria of the age range of 30-45 years, from a Swazi polygynous family setting, were employed or entrepreneur’s, completed or were pursuing a higher education qualification. Data collection consisted of qualitative research instruments namely; biographical questionnaire and an individual indepth interview schedule, which followed the six steps of the Life Design career counselling intervention Model. Methodology consisted of thematic Content analysis with the Life Design Model serving as a lens for intepretation supported by literature on Career development. Research findings were captured in the following themes, focusing on their effects on career life design: (a) Swazi culture with sub-theme of cultural expectations, (b) polygynous family upbringing with subthemes of female parental role and male parental role and (c) career life design for Swazi women with subthemes of conceptions of work life, adaptability and concept of self. Implications of the study refer to the requirement for researchers, career counsellors and practitioners in the Psychology field to consider the idea that understanding how cultural role salience and non-salience is significant in the career life design of women as one of the multiple approaches that can facilitate the process of gender equality and transformation in the workplace. The application, therefore, of career counselling interventions such as the Life Design Model presents an opportunity for gaining this understanding from the narratives of the very clients facing work life challenges and by so doing thus facilitating the reconstruction of purposeful career identities. 4 Key words: Swazi culture, career development, life designing, women, patriarchy, meaning making, adaptability, role enactment, polygynous family, Life Design Model (LDM).